MATHEMATICAL MODEL AND ALGORITHM DEVELOPMENT OF REFUELING LOCATION PROBLEM IN BUS RAPID TRANSIT NETWORK SYSTEM - RIA ATMANEGARA (NIM: 23414022), CYTRA
This research presents refueling location problem in bus rapid transit (BRT) network system with heterogeneous vehicles, vehicle tour duration and driving range are being taken into consideration. This kind of problem is faced by PT. X as BRT management company. PT. X has to determine where to locate and allocate the alternative fuel station in order to support the vehicle performance while minimize the deadmiles cost. In this research, a mathematical flow-based set covering model will be develop to solve the refueling location problem in BRT network system with heterogeneous vehicles, vehicle tour duration and driving range. The mathematical model is complex, hence branch and bound algorithm only satisfy small instance problem. To tackle the real-sized problem, density-based clustering algortihm (DBCA) is proposed.